The Analysis of Students’ Critical Thinking Skills in Determining Plane Figure Properties (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
The plane figure is compulsory mathematics material at all levels of education, including junior high school. However, students still make frequent mistakes in understanding the plane figures' properties. In understanding this topic, students must have the skill to think critically. Critical thinking is a process of rational thinking before deciding or taking action in a more specific direction. Therefore, this study aims to determine students' skills in defining the plane figure's properties. The method used in this research is a qualitative research method. Tests and interviews were used to determine the students' skills in determining the properties of the plane figure. Researchers determined five indicators used to determine students' skills in determining the nature of the plane figure: focusing and formulating, observing and assessing observation results, making and assessing inductions, defining and assessing definitions, and integrating decisions. Three junior high school students were selected as research subjects with high, medium, and low skill levels, respectively. The data analysis used descriptive analysis using method triangulation and theory triangulation. The research results show two students' mathematical critical thinking patterns based on their skills. The subjects with high and medium skills can solve all problems with a small error rate and fulfill all predetermined critical thinking skills indicators. On the other hand, the subject with low skills has not been able to solve problems, so no critical thinking indicators are met. There is a misunderstanding on high and moderate skills subjects. Neither understand the meaning of opposite angles and parallel lines in specific plane figures. It can be a reference for teachers to improve students' understanding of mathematical concepts.